Elected member of European Association of Extended Realities Advisory Board - Michael-Grigoriou, Despina (My University, 2026)
Assoc. Prof. Despina Michael-Grigoriou has been elected to the Advisory Board of the European Association of eXtended Realities! The elections took place during the General Assembly of the association (November 6–10, 2024) through secret ballot. Her term will run from January 2025 to December 2027. The results were proudly announced at the Ordinary General Meeting on November 28, 2024, during the EuroXR 2024 conference. https://www.euroxr.org/organisational-structure "The Advisory Board consists of 5 to 15 members elected by the General Assembly for a mandate of three years"
Keywords: Sciences